Analisis Strategi Pemasaran Sorgum Oleh PT. Paya Pinang Group Dalam Mendukung Gerakan Diversifikasi Pangan Lokal - Namira Azani; Zuhrinal M. Nawawi; Nur Ahmadi Bi Rahmani (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to determine and analyze how sorghum marketing strategy used by PT Paya Pinang Group in supporting the movement of local food diversification. The sampling method is done purposively by analyzing the marketing mix Strategy (product, price, place, promotion) that has been used by the company. This study is not only analyzed using qualitative descriptive also use SWOT analysis (Strenght, Weakness, opportunity, Threat). SWOT analysis is an analysis used to evaluate the opportunities and threats in the external environment as well as the strengths and weaknesses that the internal environment of the company has. The results of this study showed that IFAS score of 2.75 indicates a strong internal position, EFAS score of 2.85 indicates that the company responds to existing opportunities in a good way and is able to avoid threats in its industrial market. In the Cartesian diagram shows the position of the company in an aggressive state that is very profitable for the company. The marketing strategy used by the company to introduce sorghum as a diversification of local food crops is by expanding market share to various regions by utilizing the strength of the company in the form of good relations and transparency with suppliers and taking opportunities by utilizing the production of sorghum plants that are easy to live making production costs also minimum so as to help maximize sales profits.